Pemberdayaan Ibu Balita Stunting Melalui Pelatihan Limbah Kain Perca Untuk Peningkatan Pendapatan Keluarga - Indarwati, Indarwati; Erika, Civi; Susilowati, Tri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The main objective of this community service program is to provide sewing training that utilizes fabric waste (patchwork) for housewives who have stunted children. Through this training, it is expected that the housewives will not only gain sewing skills but also earn additional income, enabling them to improve their children’s welfare by providing nutritious food to prevent stunting. Several toddlers in Kedungan Village, Pedan Subdistrict, Klaten, are known to be affected by stunting. There are various factors contributing to stunting among these children, one of which is economic limitation. In Kedungan, the majority of mothers of stunted toddlers work full-time to support the family’s economy. As a result, childcare and attention to nutrition are not optimal. This condition is worsened by limited financial resources, which restrict access to nutritious food. Kedungan Village and its surrounding areas are known as centers of small-scale T-shirt and tailor home industries. This home industries produce fabric waste every day, which usually ends up in the trash. Therefore, our Community Service Team provides a solution and contributes through a program aimed at empowering mothers of stunted toddlers by processing fabric waste into handicrafts with economic value. The expected outcome of this community service program is that mothers with stunted toddlers will gain sewing skills and learn to process fabric waste into sellable products, thereby increasing their family income. The methods used in this program include surveys and interviews. The results of this community service program show that the activities ran smoothly. The materials were delivered effectively; participants understood the lessons, actively asked questions, and followed the training according to the instructor’s guidance. The products created by the housewives through this program include doormats, hair scrunchies, bags, and pillowcases. The output of this community service program (PKM) is the marketing of these products through an official website under the brand name “Omah Gombalmu”.